Structural Analysis of Key Factors Influencing the Sustainability of Urban Green Spaces in Palembang City Using MICMAC Approach - Syaifullah, Ahmad; Efriani, Betharia; Manurung, Sabam Syahputra (Pattimura Proceeding, 2026)
As a vital component of the urban ecosystem, green open spaces (GOS) play crucial ecological, social, and aesthetic roles in maintaining the balance of the city environment. The importance of GOS is also mandated by local regulations concerning the spatial planning of Palembang City, which affirm the government’s commitment to sustainable urban management. In formulating policy foundations related to GOS, regional governments often face strategic challenges in determining where to begin, which actions are most effective, and in what direction the policies should be directed. This study aims to identify and analyze the structural interrelationships among key factors influencing the sustainability of urban green open spaces in Palembang City, in order to provide a comprehensive analysis of the systemic dynamics underlying the effectiveness of GOS management policies. This research employs a structural analysis approach using the MICMAC (Matrix of Cross Impact Multiplication Applied to Classification) method to examine the causal relationships and the patterns of influence and dependence among 20 variables categorized into four dimensions of sustainability: (1) governance and policy, (2) physical and environmental aspects, (3) social aspects and community participation, and (4) economic and financial aspects. The results show that seven variables: urbanization and population density, spatial law enforcement, urban land value, government budget allocation, land-use change, land availability, and inter-agency coordination, constitute the primary driving factors with the highest direct influence on the system. These variables exert strong structural power and therefore form the strategic foundation for strengthening GOS governance and ensuring long-term spatial sustainability. In terms of priority ranking, urbanization and population density emerged as the most dominant factor influencing GOS sustainability. Projection of future priorities indicates rising influence for land availability, spatial law enforcement, GOS accessibility, green investment, and community-level green space provision, reflecting a growing need to safeguard spatial integrity, strengthen legal compliance, and enhance public access to green infrastructure. The identification of these key factors can serve as a valuable reference for stakeholders in making informed decisions and developing integrated strategies for sustainable urban green space management.